2017
DOI: 10.1007/s13193-016-0617-y
|View full text |Cite
|
Sign up to set email alerts
|

The Azygous Lobe of the Lung: in the Case of Lung Cancer

Abstract: The azygous lobe of the lung is an uncommon developmental anomaly. Its surgical importance is hardly being described in literature. Here, we are presenting a case of lung cancer with incidental azygous lobe, with its surgical relevance during lung cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Denega et al reported that carcinoma of the azygos lobe is not associated with regional lymph node involvement [ 8 ]. This was confirmed by Darlong et al who reported a squamous cell carcinoma arising in the azygos lobe with negative mediastinal lymph nodes [ 6 ]. Fukuhara et al described a case of a solitary nodule in an azygos lobe of the right lung, 2 cm in diameter, verified as an adenocarcinoma, again without any metastatic involvement of the regional lymph nodes and treated successfully with robot-assisted thoracic surgery [ 4 ].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Denega et al reported that carcinoma of the azygos lobe is not associated with regional lymph node involvement [ 8 ]. This was confirmed by Darlong et al who reported a squamous cell carcinoma arising in the azygos lobe with negative mediastinal lymph nodes [ 6 ]. Fukuhara et al described a case of a solitary nodule in an azygos lobe of the right lung, 2 cm in diameter, verified as an adenocarcinoma, again without any metastatic involvement of the regional lymph nodes and treated successfully with robot-assisted thoracic surgery [ 4 ].…”
Section: Discussionmentioning
confidence: 52%
“…This anomalous structure did not present with any clinical symptoms. On imaging studies, the azygos lobe may mimic an enlarged thymus, a substernal goiter, a localised pneumothorax, bulla, lung abscess, or neoplasm [ 2 , 6 - 7 ]. Diagnosing the azygos lobe may be further complicated by physiological changes in the size of the azygos vein or morphological variants of the fissure [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are described cases of an azygos lobe lung cancer-a small cell carcinoma and a non small cell carcinoma, and their surgical treatment [3,17]. It is worth noting, that in the previous studies, authors reported that the azygos lobe carcinoma is not associated with regional lymph node involvement [7], which has been repeatedly confirmed [5,18]. Although lung cancers occur in the azygos lobe, they are not very common.…”
Section: Discussionmentioning
confidence: 89%